2014
DOI: 10.1186/1471-2334-14-117
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trypanosoma cruzi infection with risk factors and electrocardiographic abnormalities in northeast Mexico

Abstract: BackgroundAmerican trypanosomiasis is a major disease and public health issue, caused by the protozoan parasite Trypanosoma cruzi. The prevalence of T. cruzi has not been fully documented, and there are few reports of this issue in Nuevo Leon. The aim of this study was to update the seroprevalence rate of T. cruzi infection, including an epidemiological analysis of the risk factors associated with this infection and an electrocardiographic (ECG) evaluation of those infected.MethodsSera from 2,688 individuals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…The median age of individuals tested positive for T. cruzi was 33 (IQR: [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The potential progression from asymptomatic (indeterminate) to the symptomatic determinate form usually occurs 10-30 years after the initial infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of individuals tested positive for T. cruzi was 33 (IQR: [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The potential progression from asymptomatic (indeterminate) to the symptomatic determinate form usually occurs 10-30 years after the initial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Because Chagas disease is also transmitted in animals, they also suggested that the introduction of the rural practices of domestic animal husbandry into peri-urban areas with poor housing conditions may have facilitated the spread of the vector. 6,21,23,24 Finally, because of stigma or discrimination against migrants and variable legal status, diminished access to health services may preclude diagnosis and treatment of Chagas disease. 6 In particular, undocumented migrants may be unwilling or unable to access health services.…”
Section: Introductionmentioning
confidence: 99%
“…The association between CD and cardiac abnormalities (stages B or more) is widely reported, however, the information is challenged by the diverse design, sample size and quality of the studies[ 19 – 24 ]. This information is largely based on outdated individual studies, and reports vary substantially among the population based studies making the scientific interpretation challenging[ 8 , 20 , 25 28 ]. Furthermore, it is known that the prevalence of different types of ECG abnormalities such as intraventricular conduction abnormalities, atrioventricular block, and arrhythmias, is higher in subjects with CD as compared to non-CD subjects, calling for its update and synthesis, which would be very useful and relevant for physicians in non-endemic countries where health care implications of CD are real and neglected[ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally considered a disease of poverty, risk of Chagas disease has been associated with housing in rural areas, of poor construction quality (e.g., palm roof, cracks in the walls), and with domestic pets and livestock in or near the house (Enger et al, 2004; Molina-Garza et al, 2014; Ramsey et al, 2005; World Health Organization, 2002). Coordinated efforts by endemic countries in the 1990’s were instrumental in shrinking the domestic vector infestation and thus the population at risk for Chagas disease (Coura and Dias; Dias and Schofield, 1999; Dias et al, 2002).…”
Section: Introductionmentioning
confidence: 99%